Petri net models for Physarum machines built to realise Boolean functions. Issue 3 (4th May 2018) - Pancerz, Krzysztof
Abstract: In the paper, we describe the possible usage of the biological substrate in the form of Physarum polycephalum in realisation of Boolean functions in their canonical forms. To extort proper behavior from the substrate, Physarum machines (biological computing devices experimentally implemented in plasmodium of P. polycephalum ) determining distribution of stimuli (attractants and/or repellents) are created. To model behavior of Physarum machines, we propose to use Petri nets with inhibitor arcs which can be treated as their high-level models. Graphical Abstract: We create Petri net models of Physarum machines built to realise Boolean functions.